2005
DOI: 10.1021/jp0580625
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Acidic Properties of MCM-41 Functionalized with Phosphate and Titanium Phosphate Groups

Abstract: Mesoporous molecular sieves Si-MCM-41 (purely siliceous) and Ti-MCM-41 (partly covered with a surface layer of TiO2) were functionalized with phosphate groups by treatment with POCl3 (denoted -MCM-41(P)and Ti-MCM-41(P), respectively). With the use of TEM, X-ray diffraction, and N2 adsorption, it was shown that the initial hexagonal structure, the high specific surface area, and porosity are retained in the functionalized materials but are not as good as in the starting materials. 1H MAS NMR and 31P MAS NMR rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 23 publications
(64 reference statements)
0
27
0
Order By: Relevance
“…In situ formation of SiP 2 O 7 happens in the presence of SiO 2 and unreacted phosphazenic components, stabilized by P 4 O 7, and is discussed in terms of organometallic decomposition to the pyrophosphate phase. Solid-state reaction of SiO 2 with phosphorus oxides gives rise to SiP 2 O 7 [34][35][36] at the macroscale. Previous routes to the synthesis of metal phosphates, using SiP 2 O 7 as a reagent, showed that the reaction of SiP 2 O 7 with metal oxides yields a solid mixture of silica and metal phosphates; its reaction with metal fluorides yields solid metal phosphates and gaseous mixtures of SiF 4 and POF 3 .…”
Section: In Situ Electron Beam-induced Nanoparticle Formationmentioning
confidence: 99%
“…In situ formation of SiP 2 O 7 happens in the presence of SiO 2 and unreacted phosphazenic components, stabilized by P 4 O 7, and is discussed in terms of organometallic decomposition to the pyrophosphate phase. Solid-state reaction of SiO 2 with phosphorus oxides gives rise to SiP 2 O 7 [34][35][36] at the macroscale. Previous routes to the synthesis of metal phosphates, using SiP 2 O 7 as a reagent, showed that the reaction of SiP 2 O 7 with metal oxides yields a solid mixture of silica and metal phosphates; its reaction with metal fluorides yields solid metal phosphates and gaseous mixtures of SiF 4 and POF 3 .…”
Section: In Situ Electron Beam-induced Nanoparticle Formationmentioning
confidence: 99%
“…3 that the intensity at 960 cm -1 increases with increasing P content. This may be a consequence of the replacement of SiO-H by SiO-P [22]. Intensity (a.u.)…”
Section: Resultsmentioning
confidence: 99%
“…4e), the 31 P NMR spectrum showed a well-resolved spectrum, characteristic of a well crystalline material. The existence of lines at −38.6, −40.5, −42.9, −44.5, −46.15, −49.48 and −52.35 ppm can be associated with the presence of several crystallographic sites for phosphorus atoms in a 3 × 3 × 3 crystal structure of TiP 2 O 7 [29]. A minor and narrow peak at ∼−27 ppm appeared at 900°C.…”
Section: P Mas-nmr Studiesmentioning
confidence: 92%